Purpose, place, and people: How the pandemic helped foster open and inclusive course design - Benjamin K. Haywood; Diane E. Boyd; John A. McArthur (To Improve the Academy)
In the spring of 2020, many institutions of higher education rapidly adopted new models of course delivery to support the ongoing need for instructional flexibility in response to the SARS-CoV-2 pandemic. This article discusses how the transition to a flexible instructional model at Furman University created space for faculty to consider the value of intentional learning environment design to meet students where they are both literally and figuratively. Reporting on a course planning framework focused on the alignment of learning outcomes, learning space, and considerations of student engagement and accessibility, this article reviews data from a faculty survey on pedagogical adaptations to highlight how the pandemic provided an opportunity to expand notions of educational architecture in course design efforts by reimagining how, where, and through which mediums teaching and learning occur. The results presented underscore the need for sustained attention to open educational architecture as a part of course and curriculum development beyond the period of pandemic teaching and reveal important considerations for educational developers working to support inclusive pedagogy in the 21st century.